Temporal and spatial dynamics of Lutjanus cyanopterus (Pisces: Lutjanidae) and L. jocu spawning aggregations in the United States Virgin Islands - Kadison, Elizabeth (2006)
The Grammanik bank is a deep reef (35-40 m) located approximately 14 km south of St. Thomas USVI, on the southern edge of the Puerto Rico shelf. The relatively narrow 1.5 km long reef annually hosts spawning aggregations of several species of groupers, snappers and jacks. Until February of 2005, when temporary seasonal protection was offered by the Caribbean Fisheries Management Council, the bank was subject to moderate or heavy exploitation from fishers. Cubera snapper (Lutjanus cyanopterus) were observed aggregating on the Grammanik bank in relatively large numbers from 2003 to 2005 and dog snapper (L. jocu) aggregations were observed in 2005. The arrival and departure of these aggregations appeared to be seasonal and to revolve around the moon phase. Cubera snapper spawning seasonality coincided with that elsewhere in the Caribbean and off south Florida. Schools of up to 1000 fish of each species were observed as well as pre-spawning behavior and milt release. Aggregations of both species showed high site fidelity within seasons but cubera snapper aggregations sites moved between seasons. The authors recommend year-round closure of the Grammanik bank based on its importance as critical fish habitat and a multi-species aggregation area. Rev. Biol. Trop. 54 (Suppl. 3): 69-78. Epub 2007 Jan. 15.